(untitled) (Numerus academy review, 2026)
The issue of constitutionalizing rights and public liberties within the content of the constitution is one of the most important guarantees granted to their exercise within the framework of the law. This study aims to clarify the scope of the constitutional court’s control in the field of protection of public rights and freedoms, and to emphasize the need to reconcile the protection of these rights and freedoms with the discretion of the legislator.